Multiscale simulation of spectroscopic properties of B3PYMPM--CBP exciplexes in OLEDs - Dubinets, Nikita Olegovich; Freidzon, Alexandra Ya (Mendeleev communications, 2025)
Using polarizable continuum model, QM/MM and effective fragment potential (EFP) approaches, exciplex luminescence at the interface of two organic semiconductors, electron transporter B3PYMPM and hole transporter CBP, was simulated taking into account their environment. The effects of multiple nonequilibrium molecular conformations in the sample and the polarizable environment of the chromophores were analyzed. It was found that EFP provides the best description of the environment, making it possible to include both structural effects and molecular polarizability.